2021
DOI: 10.1186/s12884-021-04050-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pregnancy outcomes during the COVID-19 lockdown in Iran

Abstract: Background The Covid-19 pandemic response is influencing maternal and neonatal health care services especially in developing countries. However, the indirect effects of Covid-19 on pregnancy outcomes remain unknown. The aim of the present study was to compare pregnancy outcomes before and after the beginning of the Covid-19 pandemic in Iran. Methods We performed a retrospective analysis of the medical records of 2,503 pregnant women with singleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…However, studies conducted in high-income countries or in single-center suggested the pandemic would reduce the risk of PTB ( 24 , 25 ). The researchers have proposed that COVID-19 related lockdown may cause socio-environmental and behavioural modifications, including maternal workload reduction, improved air quality, reduced maternal non-COVID-19 related infections, reductions in physical activity and better nutritional support, thus paly a role in pregnancy prolongation and exert a benefical impact on preterm birth ( 3 , 5 , 26 , 31 ). On the other hand, several recent studies have shown that COVID-19 pandemic related stressors and quarantine measures have exacerbated perinatal anxiety and depression ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies conducted in high-income countries or in single-center suggested the pandemic would reduce the risk of PTB ( 24 , 25 ). The researchers have proposed that COVID-19 related lockdown may cause socio-environmental and behavioural modifications, including maternal workload reduction, improved air quality, reduced maternal non-COVID-19 related infections, reductions in physical activity and better nutritional support, thus paly a role in pregnancy prolongation and exert a benefical impact on preterm birth ( 3 , 5 , 26 , 31 ). On the other hand, several recent studies have shown that COVID-19 pandemic related stressors and quarantine measures have exacerbated perinatal anxiety and depression ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies observed no significant difference in low birth weight (<2,500 g) associated with the pandemic ( 24 ). The COVID-19 lockdown and population response measures, as well as risk factors for adverse birth outcomes, vary from region to region, which may partly explain the differences between studies ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…CS rates have fluctuated in the geographical areas of the study region at the study time and have decreased in comparison to the start point of the study time in 2016. This decrease can have several reasons; some studies have highlighted the effect of fear of COVID-19 infection on reducing CS on maternal request [51]. Furthermore, some researchers have noted that the implementation of governmental CS restriction guidelines since 2015 in Iran has reduced the rate of CS in public hospitals in recent years [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the number of requests for in utero transfers because of threatened preterm birth and fetal growth restriction decreased during lockdown. Many authors have reported a significant impact of the pandemic, and more specifically, of the different lockdowns on preterm delivery rates and on low-birth-weight births [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies show a decrease in the number of preterm births during successive lockdowns.…”
Section: Discussionmentioning
confidence: 99%